Comparison of three types of warm-up upon sprint ability in experienced soccer players - Roland van den Tillaar; Eirik Lerberg; Erna von Heimburg (Elsevier, 2019)
Purpose: The study aimed to compare the effects of a long general warm-up, a long specific warm-up, and a short specific warm-up upon sprint ability in soccer players. Methods: Twelve male soccer players (age: 18.3 ± 0.8 years, mean ± SD; body mass: 76.4 ± 7.2 kg; body height: 1.79 ± 0.05 m) conducted 3 types of warm-ups with 1 week in between: a long general warm-up, a long specific warm-up, and a short specific warm-up followed by 3 sprints of 40 m each. The best, average, and total sprinting times together with heart rate and ratings of perceived exertion were measured. Results: The sprint times (best, average, and total time) were significantly better when performing a long specific or short specific warm-up compared with the long general warm-up (all p < 0.05). The received perception exertion was significantly lower during the specific short warm-up (4.92 ± 0.90) compared with the longer ones (6.00 ± 0.74 and 6.25 ± 0.87, respectively). Conclusion: Specificity is more important in a warm-up routine before sprint performance than the duration of the warm-up. Keywords: Duration, Performance, Received perception exertion, Running, Specificity, Total sprinting times